2008
DOI: 10.1021/pr800751x
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycoside Biomarker of Apolipoprotein C3: Responsiveness to Obesity, Bariatric Surgery, and Therapy with Metformin, to Chronic or Severe Liver Disease and to Mortality in Severe Sepsis and Graft vs Host Disease

Abstract: The glyco-isoforms of intact apolipoprotein C3 (ApoC3) were used to probe glycomic changes associated with obesity and recovery following bariatric surgery, liver diseases such as chronic hepatitis C (CHC) and alcoholic liver cirrhosis, as well as severe, multiorgan diseases such as sepsis and graft vs host disease (GVHD). ApoC3 glyco-isoform ratios responded to unique stimuli that did not correlate with serum lipids or with other blood components measured in either a control population or a group of extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 46 publications
4
49
2
Order By: Relevance
“…These accurate mass fragment ions localized the O-glycosylation modification to the C-terminal end of this protein between the c 58 and c 77 ions (Asp 59 -Val 77 ) as shown in Fig. 5A, consistent with other findings showing Thr 74 to be the site of modification (36,37). Additionally, high-resolution threshold dissociation methods (i.e., CAD) revealed seven and three matching b and y fragment ions, respectively, with the predominant fragmentation being the selective removal of the sugar side chain (−291.09 Da, −656.20 Da), supporting the presence of an O-glycosylation modification (Fig.…”
Section: Resultssupporting
confidence: 90%
“…These accurate mass fragment ions localized the O-glycosylation modification to the C-terminal end of this protein between the c 58 and c 77 ions (Asp 59 -Val 77 ) as shown in Fig. 5A, consistent with other findings showing Thr 74 to be the site of modification (36,37). Additionally, high-resolution threshold dissociation methods (i.e., CAD) revealed seven and three matching b and y fragment ions, respectively, with the predominant fragmentation being the selective removal of the sugar side chain (−291.09 Da, −656.20 Da), supporting the presence of an O-glycosylation modification (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Changes in the ratio of apoC-III glyco-isoforms have also been demonstrated in other diseases (51). Moreover, changes in the glycosylation of (serum) proteins in general have been observed in a variety of liver diseases (52).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, a recent MS study of 96 serum samples showed that 30 % of the individuals displayed an apoC-III pattern with additional glycosylated variants, characterised by fucosylation (Nicolardi et al 2013b). The relevance of these glycosylated non-sialylated variants of apoC-III, as of the C-terminal truncated forms, is yet unclear, but may explain somewhat contradictory results showing higher relative levels of non-and lesssialylated apoC-III in obese subjects than in lean subjects (Harvey et al 2009;Karlsson et al 2009), although obesity is generally associated with high triglyceride levels.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%